Labour justice : A constitutional evaluation of labour law - Routh, Supriya (New Delhi : Cambridge University Press, 2024)
This book argues that the imagination of the worker-citizen, inherent in citizens' constitutional duty to work, is the very foundation of constitutional citizenship and its social justice agenda. The design of social justice in the constitution takes labour as its core ideological and political commitment, seeking to treat workers fairly for their social contribution through work. Employing this constitutional design, this book evaluates the recently repealed labour law against the constitutional metric of social justice. Drawing on the components of social justice, the book evaluates the new labour law in its capacity to promote market-based distribution, respecting basic individual liberties; the complementary redistribution of public goods, upholding the principle of solidarity; and worker participation in decisions about the operation of the market and the state. In offering such evaluation, the book conceives of work in its wider social relationship in contrast to its narrower private exchange rationale.
Keywords: Labour law; Business economics